ศาลปกครองกับหลักกฎหมายทั่วไปในทางปกครอง (ศึกษาเปรียบเทียบประเทศฝรั่งเศสและประเทศไทย) - กนกวรรณ อิทธิวิภาต (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
This thesis explors the relationship between the general principle of administrative law and the administrative jurisdiction in both France and Thailand. In order to make a decision, the administrative court considers that the administrative law is the primary source to be applied. It is because the concept of administrative law is to maintain public interests. Thus, the general principle of administrative law, which is applied by the court, should be consistent with this concept. According to the research, both France and Thailand use the same system: dual jurisdiction. Nevertheless, the French administrative law has been developing longer than the Thai administrative law. The French general principle of administrative law is crystallized correspond with its society. Therefore, it is easily accepted and applied by administers. On the other hand, the later Thai administrative law needs more general principle of administrative law in order to deal with social problems. By comparing the general principle of administrative law in both countries, it can be seen that many French general principles of administrative law were adapted to Thailand. However, some principles still have not yet been seen in Thailand. This thesis gives some suggestions to develop the general principle of administrative law in Thailand by creating better understanding to the public. Furthermore, in order to emphasize the general principle of administrative law in Thailand, this thesis suggests that the administrative judges should apply it without prejudice and adapt general principles of administrative law from other countries to develop the Thai system